163k views
0 votes
Can someone solve these rational expressions showing work thanks

Can someone solve these rational expressions showing work thanks-example-1
User Lsimmons
by
5.2k points

1 Answer

1 vote

Answer:


(x-5)/(\left(x-3\right)\left(x+2\right))+(2)/(\left(x-3\right)\left(x+2\right))=(1)/(2+x)

Explanation:


(x-5)/(\left(x-3\right)\left(x+2\right))+(2)/(\left(x-3\right)\left(x+2\right))


\mathrm{Apply\:rule}\:(a)/(c)\pm (b)/(c)=(a\pm \:b)/(c)


=(x-5+2)/(\left(x-3\right)\left(x+2\right))


\mathrm{Add/Subtract\:the\:numbers:}\:-5+2=-3


=(x-3)/(\left(x-3\right)\left(x+2\right))


\mathrm{Cancel\:the\:common\:factor:}\:x-3


=(1)/(2+x)

User Dhalfageme
by
4.5k points